Studi Nilai dan Distribusi Biodiversitas di Daerah Aliran Sungai (DAS) Ciliwung Hulu - WAHYUNI, SRY; WIJAYA, SYARTINILIA (Jurnal Arsitektur Lansekap, 2015)
ABSTRACT Study of Biodiversity Value and Distribution in The Upper Stream of Ciliwung Watershed Watershed is one of the ecological boundary that has important role related to landscape sustainability. Ciliwung Watershed is categorized as super-priority watershed in Indonesia and provides landscape services particularly mentioned in this study is biodiversity value.The study sites were located in three sub-districts in the upper stream of Ciliwung Watershed (Ciawi, Megamendung, Cisarua), Bogor District of West Java. The main objectives of this study were to analyze value and distribution of biodiversity using six indicators of landscape sustainability. The six indicators (presence of threatened species, land use and land cover change, land use intensity of organic agricultural, population, occupation, and infrastructure) were analyzed using geographical information system (GIS). Based on the result, it can be shown that Cisarua and Megamendung sub-district are the first and second largest area with high biodiversity value (4.022 Ha and 2.099 Ha). Meanwhile, Ciawi sub-district has no area with high biodiversity value. Finally, we propose six recomendations of landscape management for biodiversity sustainability in the upper stream of Ciliwung Watershed.   Keywords:biodiversity value, Ciliwung Watershed, landscape service, GIS, landscape management